NEED ANALYSIS FOR ENGLISH COMPETENCY-BASED BUSINESSES THROUGH INTENSIVE LEARNING PROGRAMS - Ronald M. P. Silalahi (Universitas Pelita Harapan, 2022)
The urgency of mastering English in Indonesia is very high. This phenomenon reflects the rapid development of technology in recent decades. On the other hand, English proficiency in Indonesia is still very low. Formal educational institutions for elementary, junior high, high school, and university still cannot answer students' needs for quality English. Therefore, there is a desire to enrich English competence through Intensive Courses. This condition can be seen as an opportunity for educational-based entrepreneurs who want to develop their businesses in a non-academic context. Before building a language competency-based business, a mapping of prospective students' needs is essential. This article involves 152 students as respondents to find out the current learning needs of students. Questionnaires were distributed with the aim of (1) providing an overview of the things students need and want, referring to the knowledge they have; (2) describing students' current English language skills; (3) Learning needs are related to what must be done to learn. This questionnaire analyzes the things that need to be developed in an English language course that can answer and facilitate students' needs. The results are that English courses should focus on conversation and writing skills to support students' work and academic needs.